Sapto Darmo dan Kearifan Lokal: Kajian Filosofis dan Praktik Ritual - Nahar Surur (3026-1791, 2025)
This article discusses the teachings and ritual practices in the Sapto Darmo belief in the context of local wisdom. Sapto Darmo is a belief system that emphasizes balance, simplicity, and respect for ancestors as part of the spiritual values ​​of Indonesian society. This study explores the philosophical aspects underlying the teachings of Sapto Darmo and how its ritual practices contribute to the spiritual and social lives of its followers. Through a descriptive approach and qualitative analysis, this article highlights the role of Sapto Darmo in shaping cultural identity and its relevance in modern life. By understanding the teachings and rituals in this belief, it is hoped that it can provide broader insights into spiritual diversity in Indonesia.